Abstract random differential equations with state-dependent delay using measures of noncompactness - Heris, Amel; Bouteffal, Zohra; Salim, Abdelkrim; Benchohra, Mouffak; Karapınar, Erdal (Nonlinear Analysis: Modelling and Control, 2024)
This paper is devoted to the existence of random mild solutions for a general class of second-order abstract random differential equations with state-dependent delay. The technique used is a generalization of the classical Darbo fixed point theorem for Fréchet spaces associated with the concept of measures of noncompactness. An application related to partial random differential equations with state-dependent delay is presented.